User-Friendly Level Differences in Learning Mathematics Using Braille Books with Talking Books for the Student with Visual Impairment - Subagya (Lembaga Penelitian dan Pengabdian kepada Masyarakat, 2022)
Learning media for students with visual impairment affects the speed and process of understanding in learning. The use of Braille books and talking books have advantages and disadvantages of each. This study aims to examine the difference in user-friendly levels of students with visual impairment learning mathematics using Braille books and talking books. This research approach uses a quantitative with the design used in this study being a quasi-experimental-posttest-only Control design. The subjects in this study were 38 students consisting of 8 special schools in 6 provinces in Indonesia. Data collection techniques used questionnaires and tests. The validity of the instrument uses content validity and the reliability test using the interpreter technique. The data analysis technique used in this experimental research is t-test or t-test data analysis. The results show that the use of braille books has a significant difference from talking books. The difference is shown by the t count of -4.955 with sig 0.00 which means that there is a significant difference between the use of Braille books and speaking books in gaining ease of learning.